SnapMove: Movement Projection Mapping in Virtual Reality - Cohn, Brian; Maselli, Antonella; Ofek, Eyal; Gonzalez Franco, Mar (IEEE AIVR 2020, 2020)
We present SnapMove a technique to re-project reaching movements inside Virtual Reality. SnapMove can be used to reduce the need of large, fatiguing or difficult motions. We designed multiple reprojection techniques, linear or planar, uni-manual, bi-manual or head snap, that can be used for reaching, throwing and virtual tool manipulation. In a user study (n=21) we explore how if the self-avatar follower effect can be modulated depending on the cost of the motion introduced by remapping. SnapMove was successful in re-projecting user’s hand position from e.g. a lower area, to a higher avatar-hand position—a mapping which can be ideal for limiting fatigue. It was also successful in preserving avatar embodiment and gradually bring users to perform movements with higher cost energies, which have most interest for rehabilitation scenarios. We implemented applications for menu interaction, climbing, rowing, and throwing darts. Overall, SnapMove can make interactions in virtual environments easier. We discuss the potential impact of SnapMove for application in gaming, accessibility and therapy.